Inorganic Scaling in Membrane Desalination: Models, Mechanisms, and Characterization Methods - Rolf, Julianne; Cao, Tianchi; Huang, Xiaochuan; Boo, Chanhee; Li, Qilin; Elimelech, Menachem (American Chemical Society, 2022)
Inorganic scaling caused by precipitation of sparingly soluble salts at supersaturation is a common but critical issue, limiting the efficiency of membrane-based desalination and brine management technologies as well as other engineered systems. A wide range of minerals including calcium carbonate, calcium sulfate, and silica precipitate during membrane-based desalination, limiting water recovery and reducing process efficiency. The economic impact of scaling on desalination processes requires understanding of its sources, causes, effects, and control methods. In this Critical Review, we first describe nucleation mechanisms and crystal growth theories, which are fundamental to understanding inorganic scale formation during membrane desalination. We, then, discuss the key mechanisms and factors that govern membrane scaling, including membrane properties, such as surface roughness, charge, and functionality, as well as feedwater characteristics, such as pH, temperature, and ionic strength. We follow with a critical review of current characterization techniques for both homogeneous and heterogeneous nucleation, focusing on the strengths and limitations of each technique to elucidate scale-inducing mechanisms, observe actual crystal growth, and analyze the outcome of scaling behaviors of desalination membranes. We conclude with an outlook on research needs and future research directions to provide guidelines for scale mitigation in water treatment and desalination.